Investigation of the Blowout Preventer (BOP) for the Drill String - Omarova, A.Sh. (Herald of Azerbaijan Engineering Academy, 2025)
In the conditions of high pressure, the task of drilling column ejection is considered. From the solution of differential equation of drilling pipes columns at known values of parameters of ejection of a boring column bottom hole pressure, calling this out-break is defined.